English Teaching Peculiarities of Faculty of Arts Students on «Fine Art» Specialty at Khmelnytskyi Humanitarian-Pedagogical Academy - Hlushok, Liudmyla (Pedagogical Discourse, 2014)
The article deals with the problem of professionally oriented foreign language training of Bachelor degree students on «Fine Art» specialty of the Faculty of Art at Khmelnytskyi Humanitarian Pedagogical Academy in particular. The author determines the degree of the given problem research at present stage, the importance of communicative, personal and professionally oriented prospective professionals training with the purpose of their effective communication in academic and work-related environments in fine arts domain has been outlined. The peculiarities of the course «English for Professional Purposes», particularly the professionally oriented course content, teaching and methodological aids have been analyzed in the article. The process of formation of grammatical and lexical competence, professional reading and writing skills with the help of precisely defined subject matter of professionally oriented texts, determined terminological lexis and complex of lexical and grammatical exercises, dictionaries has been described in details. The necessity of the use of interactive and IT educational technologies, gaming technique are identified too.